COVID-19 vaccine booster hesitancy among the elderly in Malaysian residential care homes: a cross-sectional study in Klang Valley - Lee, Kai Wei; Yap, Sook Fan; Ong, Hooi Tin; Liew, Sien Leong; Oo, Myo; Swe, Kye Mon Min (MDPI AG, 2024)
The elderly are considered a high-risk group for severe outcomes and death from COVID-19 infection. Given the emergence of new COVID variants and the immunity provided by vaccines waning over time, booster doses of the vaccine have been advocated for those at risk to stay protected. This study aimed to determine the factors associated with hesitancy toward the second booster of the COVID-19 vaccine among the elderly residing in residential care homes. A cross-sectional study was conducted in 24 residential care homes in the Klang Valley using a face-to-face interview questionnaire. The study population included individuals aged 60 and above who had been fully vaccinated against COVID-19 up to the first booster dose. Second-booster hesitancy was assessed using the Oxford Vaccine Hesitancy Scale with seven items, the aggregate score of which ranges from seven to thirty-five; the higher the score, the greater the level of hesitancy. Multivariate linear regression was employed to determine factors associated with second-booster hesitancy, and a p-value < 0.05 was considered statistically significant. Data from 401 elderly individuals were included for analysis. The mean score of the Oxford Vaccine Hesitancy Scale was 21.6 ± 7.2. Predictors of second booster hesitancy were identified. Age, Indian ethnicity, being a recipient of the Sinovac vaccine as the first COVID-19 booster, experiencing the death of close friends or immediate family members following COVID-19 vaccination, and negative messages (indicating that taking a booster dose is harmful) from caregivers, friends, or family members were found to be associated with an increased second-booster-hesitancy score. Conversely, positive messages (indicating that taking a booster is helpful) from the government and caregivers, friends, or family members were identified as predictors associated with a reduction in the second-booster-hesitancy score. While vaccines effectively combat severe COVID-19, the majority of the elderly hesitate before taking the second booster. Their hesitancy, rooted in the perception of a low self risk and reliance on protection from the initial doses, emphasizes the need for intervention by relevant bodies. Taking into consideration the risk, albeit relatively low, of potentially serious side effects following COVID-19 vaccinations, it is imperative that transparent, appropriate, and positive messaging regarding booster vaccines, particularly in the context of the elderly from residential care homes, be available. Encouraging this high-risk group to embrace the second booster aligns with the goal of maximizing protection within the vulnerable elderly population.